Pulmonary Lymphangitic Carcinomatosis of Small Cell Lung Carcinoma: An Autopsy Case Report - Albuquerque, Ronniel Morais; Mello, Gabriela Naccarati de; Lopes, Maria Clara Nascimento; Gomes, Murilo Lima; Neto, Amaro Nunes Duarte (Brazilian Journal of Case Reports, 2025)
Pulmonary lymphangitic carcinomatosis is characterized by the involvement of pulmonary lymphatic vessels by tumor cells. This work reports the autopsy findings of a 53-year-old woman who presented with subacute constitucional symptoms and presence of numerous nodules throughout the body. Chest CT revealed heterogeneous posterior mediastinal mass involving thoracic structures and pulmonary findings suggestive of lymphangitic spread. Before further diagnostic evaluation could be performed, the patient suffered from rapid clinical deterioration, which resulted in her death. Autopsy revealed a posterior mediastinal mass with marked pulmonary lymphatic involvement by neoplastic cells. Immunohistochemical analysis demonstrated positivity for CAM5.6, CD56 and Ki67, consistent with a high-grade neuroendocrine tumor. Metastatic involvement was also observed in the heart, adrenal, pancreas, duodenum and bone marrow. The final autopsy diagnosis was pulmonary thromboembolism as the immediate cause of death, in the context of a highly aggressive small lung cell carcinoma with pulmonary lymphangitic spread.